Efficacy of Caregivers’ Intervention on Recovery of Head Injury Cases in India - Verma, Kirti; Shruti; Tewari, Manoj Kumar; Kaur, Sukhpal; Ghai, Sandhya (Indian Journal of Neurosurgery, 2018)
Background Patients with head injury are discharged from hospitals in a dependent state. In the home care settings, the caregivers have to take care of the patients. In India, there is scarcity of data on interventions of family caregivers of persons with head injuries.Objective To assess the efficacy of an instructional module for caregivers of patients with head injury on recovery of the patients.Method The study was performed at the Neuro-Surgery Department of Post Graduate Institute of Medical Education and Research (PGIMER), Chandigarh, India. Total 82 patients with 41 each in experimental and control groups and their caregivers were included in the study. The caregivers of patients in experimental group were demonstrated procedures related to care of a dependent patient. An instructional module containing guidelines regarding personal hygiene, catheter care at home, prevention of bedsores, tracheostomy suctioning at home, range-of-motion exercises, care of surgical wound, and discharge instructions regarding medication and follow-up was given to the caregivers in experimental group. The efficacy of intervention was assessed on occurrence of fever, chest infection, eye infection, bedsores, wound infection, constipation, urinary tract infection, deep vein thrombosis, length of stay, and readmission in hospital in both the groups.Results Occurrence of fever, constipation, and length of stay were reduced significantly in experimental group. A reduction in the rates of chest infection, bedsore development, wound infection, and urinary tract infection were also noted in experimental group.Conclusion The study shows that training the caregivers of head injury patients enhances the recovery and prevents complications in the patients.
Keywords: head injury; educational intervention; recovery outcomes